Congenital Cleft Hand and Foot: Review of the Literature and Report of Two Cases - Okur, M. İhsan; Yıldırım, A. Mustafa; Köse, Rüştü (Fırat University, 2004)
Hand and foot functions of the cases with cleft hand and foot deformity are usually good. Autosomal dominant inheritance is frequently seen in case the existence of cleft hand and foot history in family. It is necessary in the therapy of the patient with cleft hand and foot both functional improvement and enhancement of the aesthetical condition, if possible. Early surgical therapy, especially in cleft foot, can prevent toe and finger deformities. Simply excision of the cleft skin and suturing of the tissues together do not give always best result. Surgical method should be chosen according to the condition of the case. Sometimes the best solution is achieved when surgery is not performed. We herein presented two cases that had congenital cleft hand and foot deformity. The both cases had bilateral cleft hand and foot. Cases were examined and evaluated but any surgical process was not performed.

Yarık el ve ayak deformiteleri bulunan olgularda el ve ayak fonksiyonları genellikle iyidir. Ailesinde yarık el ve ayak bulunan durumlarda sıklıkla otozomal dominant geçiş mevcuttur. Yarık el ve ayak olgularının tedavisinde hem fonksiyonel düzeltme hem de eğer mümkünse estetik durumun da iyileştirilmesi gereklidir. Özellikle ayak yarıklarında cerrahi tedavinin erken yapılması parmak deformitelerini önleyebilir. Basitçe yarığın cildinin çıkarılması ve dokuların bir araya getirilerek dikilmesi her zaman en iyi sonucu vermez. Cerrahi tedavi yönteminin olgunun özelliklerine göre seçilmesi gerekir. Bazen de en iyi sonuç hiç ameliyat yapılmaması ile alınır. Biz burada doğuştan yarık el ve ayak deformitesi olan iki olguyu sunuyoruz. Her iki olguda da bilateral el ve ayak yarığı vardı. Olgular muayene edilip değerlendirildi ancak bir cerrahi girişim uygulanmadı.
Doğuştan Yarık El ve Ayak: Literatürün Gözden Geçirilmesi ve İki Olgu Sunumu